POTENCY OF LUTEOLIN WITH SOLID LIPID NANOPARTICLE (SLN)-POLYETHYLENE GLYCOL (PEG) MODIFICATION FOR ARTEMISININ-RESISTANT PLASMODIUM FALCIPARUM INFECTION - Kamarullah, William; Indrajaya, Erika; Emmanuella, Janice (Institute of Topical Disease Universitas Airlangga, 2018)
Falciparum malaria is still considered as one of the important global health problems and its causal agent (Plasmodium falciparum) is reported to be the third most common factor for contributing the number of deaths in the world. As we all know, Artemisinins arethe most rapidly acting of currently available antimalarial drugs. Along with Artesunate, these two combining drugs, the so-called Artemisinin-based combination therapies (ACTs) has become the foundation of modern falciparum malaria treatment globally. Nowadays, however, there have been reports about intricate cases of resistance against Artemisinin in various Southeast Asian countries and it is predicted to spread over several other countries, including Indonesia. Therefore, adjuvant therapy is required along with first-line therapy administration to help eradicate both Artemisinin-sensitive and resistant P. falciparum. Luteolin in vitro has a prospective inhibitory activity (IC50<50 Î¼g) in inhibiting the development of parasite's life cycle. Nonetheless, its poor bioavailability and pharmacokinetics restrict clinical application. The low bioavailability of luteolin requires encapsulation using solid lipid nanoparticle (SLN) and polyethylene glycol (PEG). SLN is useful for improving the bioavailability of luteolin in the body, whereas PEG is needed in order to prevent the destruction of luteolin-SLN substance by the reticuloendothelial system. Here in this literature review, we're trying to demonstrate the benefits, potential, way of constructions, pharmacokinetics, and pharmacodynamics of luteolin encapsulated with SLN with PEG modification. Thus, it is hoped that the results of this literature study may encourage further research in assisting the development of adjuvant therapy for cases of Artemisinin-resistant P. falciparum infection.